Training on Scaling of Climate-Smart Washera and Wollo Sheep Breed Improvement Program - Getachew, Tesfaye; Belay, Berhanu; Rischkowsky, Barbara A.; Dagnew, Mulatu; Tesfa, Asemu; Haile, Aynalem (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
The International Center for Agricultural Research in the Dry Areas (ICARDA), The Amhara Regional Agricultural Research Institute (ARARI), the Accelerating the Impact of CGIAR Climate Research in Africa (AICCRA), and the Amhara Livestock and Fisheries Resource Development Office organized a workshop that took place on May 29, 2023, in Bahir Dar Ethiopia. The main goals of the workshop were assessing the advancements of already running community-based breeding programs (CBBPs) and recently formed production Units (PUs) and training livestock development agents and extension workers on managing and establishing production unit sites. The training course was attended by livestock from 16 districts in the Wollo and Gojjam areas, universities, ARARI, and regional and district-level livestock offices. Dr. Likawent Yeheyis, Deputy Director General of ARARI, gave a welcome and opening address to kick off the session. Mulatu Dagnew from the Regional Livestock Office, Asemu Tesfa from the Andassa Research Center, and Tesfaye Getachew from ICARDA each gave a presentation following that. Presentations helped to understand the development and status of CBBPs and PUs, as well as helped to understand how to create and maintain PU sites and breeding tram utilization modality. In the WaWo scaling project, 4280 households in CBBPs and Pu sites have access to the climate-smart breeding program. The training was attended by 67 people in total, 17 of them were women.